Internal On-line Partial Discharge Analysis of 68.75 MVA Generator Stator Winding Insulation - Waluyo Waluyo; Siti Saodah; Eltha Hidayatullah (International Journal of Electrical and Computer Engineering (IJECE), 2016)
Partial discharge is a phenomenon of electron ionization occurs due to concentrated electric field in a different edge plane. This phenomenon will be investigated by an electric field measurement in a measuring point. The internal partial discharge will give the insulation damage effect on a generator stator winding due to void existence. This manuscript presents the measurement results of the on-line internal partial discharge on the stator winding insulation of 68.75 MVA generator. It used the resistant temperature detector method and CM2000TM. The results were classified into three conditions based on the voids in the generator stator insulation, the internal delamination and the surface discharge.